Dry desulfurizer as well as preparation method and application thereof

By combining red mud with pore-forming agents, binders and additives, dry desulfurization agents are prepared, which solves the problems of red mud waste slag treatment and sulfur dioxide pollution, and achieves efficient and economical flue gas desulfurization effect, which is suitable for industrial applications.

CN119215649APending Publication Date: 2024-12-31TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411358002.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The problem of red mud waste slag treatment and sulfur dioxide pollution control problems, it is difficult for the existing technology to effectively use red mud for flue gas desulfurization, and traditional methods have high costs and environmental pollution risks.

Method used

Red mud is used as the main raw material, combined with pore-forming agent, binder and additive, and a dry desulfurizer is prepared through ball milling and calcining processes to treat sulfur-containing waste gas and achieve flue gas desulfurization.

Benefits of technology

It reduces the cost of waste gas treatment, realizes the effective utilization of red mud and flue gas desulfurization effect, has a simple process, is suitable for large-scale industrial promotion, and is pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215649A_ABST
    Figure CN119215649A_ABST
Patent Text Reader

Abstract

The invention relates to the field of flue gas purification technology and environmental governance, in particular to a novel dry desulfurizer based on red mud as well as a preparation method and application of the novel dry desulfurizer. The dry desulfurization agent comprises the following raw materials in parts by mass: 30-60 parts of red mud, 5-10 parts of a pore forming agent, 10-20 parts of a binder and 20-40 parts of an additive. The desulfurizer is prepared from the solid waste red mud as the raw material, a thought is provided for utilization and treatment of the red mud, the prepared desulfurizer is used for treating sulfur-containing waste gas, the waste gas treatment cost is reduced, the new measure of treating waste with waste is achieved, and the economic and environmental win-win situation is achieved. The preparation method is simple in process, free of pollution in the preparation process and easy to industrially popularize on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of flue gas purification technology and environmental management, and in particular to a novel dry desulfurization agent based on red mud, and a preparation method and application thereof. Background Art

[0002] Alumina production produces many byproducts, the most important of which is red mud. Red mud is generally red due to its high iron oxide content, and some are brown due to its low iron oxide content. Since red mud contains a large amount of alkaline compounds, fluorine, aluminum and other impurities, scientists from various countries have made little progress in the comprehensive utilization of red mud. The treatment of red mud waste has become a major problem. The main measure currently taken is to pile it up on land or on the seabed, but as the amount of red mud increases, the problems caused by storage and disposal are becoming more and more serious.

[0003] Sulfur dioxide is a major air pollutant, and is produced when coal and oil are burned. Sulfur dioxide is extremely harmful to humans, animals, plants and the atmosphere. It can damage the respiratory systems of humans and animals, corrode the branches and leaves of plants, and inhibit plant growth. In addition, sulfur dioxide is the main cause of acid rain, which can damage soil, water quality and building materials. Therefore, the control of sulfur dioxide has always been the focus of environmental protection and prevention. Summary of the invention

[0004] Based on the above content, the present invention provides a new dry desulfurizer based on red mud and its preparation method and application. The present invention utilizes red mud, an industrial waste that causes great harm to the environment, and uses it for flue gas desulfurization, uses solid waste to treat industrial waste gas, and achieves a win-win situation for the economy and the environment. The raw materials of the method of the present invention are easy to obtain, the preparation process is simple, and the desulfurizer prepared has a good desulfurization effect.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is a dry desulfurizer, wherein the raw materials include 30-60 parts of red mud, 5-10 parts of pore-forming agent, 10-20 parts of binder and 20-40 parts of additives by weight.

[0007] The second technical solution of the present invention is a method for preparing the above-mentioned dry desulfurization agent, comprising the following steps:

[0008] Mixing and ball-milling the raw materials according to their weight proportions to obtain a mixed material;

[0009] The mixed material is extruded and calcined to obtain the dry desulfurization agent.

[0010] The third technical solution of the present invention is the application of the above-mentioned dry desulfurization agent in the treatment of sulfur-containing waste gas.

[0011] The present invention discloses the following technical effects:

[0012] The present invention uses solid waste red mud as a raw material to prepare a desulfurizer, which provides ideas for the utilization and treatment of red mud. The prepared desulfurizer is used to treat sulfur-containing waste gas, which reduces the cost of waste gas treatment, realizes a new measure of "treating waste with waste", and achieves a win-win situation for the economy and the environment.

[0013] The preparation method of the invention has simple process and is pollution-free in the preparation process and is easy to be promoted on a large scale in industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0015] Figure 1 The figure is a process flow chart of the preparation process of the dry desulfurizing agent of the present invention.

[0016] Figure 2 This is a comparison diagram of the XRD of the desulfurizer prepared in Example 3 before and after desulfurization.

[0017] Figure 3 The SEM comparison pictures of the desulfurizer prepared in Example 3 before and after desulfurization; wherein (a) is before desulfurization, and (b) is after desulfurization.

[0018] Figure 4 The BET diagrams of the desulfurizers prepared in Examples 3 and 4 are shown in FIG. 1 , wherein (a) is Example 3 and (b) is Example 4.

[0019] Figure 5 The desulfurization performance diagram of the desulfurizer prepared in the examples and comparative examples; wherein a is comparative example 1-2 and examples 1-3, b is examples 1-4, and c is examples 3 and examples 5-6. DETAILED DESCRIPTION

[0020] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0021] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0022] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0023] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0024] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0025] The first aspect of the present invention provides a dry desulfurization agent, wherein the raw materials include 30-60 parts of red mud, 5-10 parts of pore formers, 10-20 parts of binders and 20-40 parts of additives in parts by mass.

[0026] Pore-forming agents can increase porosity and specific surface area, but adding too much will reduce the strength of the desulfurizer and even make it difficult to form. Binders can increase the strength of the desulfurizer and improve the desulfurization performance, but adding too much will cause the desulfurization performance of the desulfurizer to drop rapidly. Additives can effectively enhance the desulfurization performance of the desulfurizer, but excessive use will reduce the desulfurization performance.

[0027] In some embodiments of the present invention, the pore-forming agent is a polymer foamed microsphere with a particle size of 10 to 50 μm.

[0028] Polymer foam microspheres are a lightweight, non-toxic, high-strength material. Using polymer foam microspheres as pore-forming agents can increase porosity, increase specific surface area, provide sufficient reaction surface, and enhance gas adsorption. Compared with other pore-forming agents such as activated carbon, they have better desulfurization performance, and the addition of microspheres also improves the strength and impact resistance of the desulfurizer.

[0029] In some embodiments of the present invention, the binder is at least one of cellulose, sodium silicate and kaolin.

[0030] In some embodiments of the present invention, the additive is at least one of fly ash, iron powder, and calcium hydroxide.

[0031] The second aspect of the present invention provides a method for preparing the above-mentioned dry desulfurization agent, comprising the following steps:

[0032] Mixing and ball-milling the raw materials according to their weight proportions to obtain a mixed material;

[0033] The mixed material is extruded and calcined to obtain the dry desulfurization agent.

[0034] The mixing ball milling time is 3-5 hours. After ball milling, the materials can be mixed more fully, and the effective sulfur-fixing components such as Fe2O3 and Ca(OH)2 can be distributed more evenly.

[0035] Extrusion molding is the process of extruding the mixed material into strip samples of the same thickness through an extrusion die.

[0036] The red mud also includes a step of crushing and grinding to 100 mesh before mixing with other raw materials.

[0037] In some embodiments of the present invention, the calcination temperature is 400-700° C. and the calcination time is 3 hours.

[0038] After red mud is calcined at 400-700℃, a solid-phase reaction can occur, which promotes crystal transformation and the production of catalytic active iron oxide, thereby improving desulfurization activity. It can also further remove chemically bound water, improve the mechanical strength of the desulfurizer, ensure shape stability during use, and facilitate industrial use.

[0039] When the calcination temperature is lower than 400℃, the active iron oxide is not completely converted and the desulfurization activity is not greatly improved. As the calcination temperature increases, the active iron oxide gradually increases and the desulfurization performance improves. However, if the calcination temperature continues to increase, the active iron oxide will continue to be converted into Fe3O4, especially when it exceeds 700℃, which not only consumes heat sources, but also increases the degree of conversion of the active iron oxide, which will make the desulfurization effect worse.

[0040] The method further comprises a drying step before calcination; the drying temperature is 70 to 100° C. and the drying time is 1 to 3 hours.

[0041] The third aspect of the present invention provides an application of the above-mentioned dry desulfurization agent in treating sulfur-containing waste gas. The sulfur-containing components in the sulfur-containing waste gas are SO2, H2S and the like.

[0042] The detection method involved in the present invention is:

[0043] X-ray diffraction (XRD) spectra were measured using a SmartLab 9KW X-ray diffractometer, and the radiation source was Cu Kα radiation.

[0044] The sulfur content in the desulfurizer was tested by an X-ray fluorescence spectrometer from Panaak of the Netherlands to calculate the sulfur capacity.

[0045] The specific surface area and pore structure were tested using the American Micromeritics ASAP 2460 fully automatic specific surface area and porosity analyzer.

[0046] The morphology and microstructure of the samples were observed using a Hitachi Regulus8100 scanning electron microscope (SEM).

[0047] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0048] The red mud used in the embodiments of the present invention is Bayer process red mud.

[0049] The particle sizes of the polymer foamed microspheres used in the embodiments of the present invention are 10-16 μm and 35-50 μm respectively.

[0050] The fly ash used in the embodiments of the present invention is Class I fly ash.

[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0052] The process flow of preparing the dry desulfurizing agent of the present invention is as follows: Figure 1 shown.

[0053] Example 1

[0054] (1) Preparation method: Red mud, polymer foamed microspheres with a particle size of 10 to 16 μm, sodium silicate, fly ash, and calcium hydroxide are weighed in a mass ratio of 5:1:2:1.5:3, ball-milled for 4 h, and fully mixed. The mixed materials are extruded into strips, dried at 85° C. for 2 h, and calcined at 550° C. for 3 h to obtain a dry desulfurizer.

[0055] (2) Desulfurization: Grind the above dry desulfurizer and put it into the desulfurization device for desulfurization treatment, and record the desulfurization time.

[0056] Example 2

[0057] (1) Preparation method: Red mud, polymer foam microspheres with a particle size of 35 to 50 μm, sodium silicate, fly ash, and calcium hydroxide are weighed in a mass ratio of 7:1:2.5:2:4, ball-milled for 4 h, and fully mixed. The mixed materials are extruded into strips, dried at 85° C. for 2 h, and calcined at 550° C. for 3 h to obtain a dry desulfurizer.

[0058] (2) Desulfurization: Grind the above dry desulfurizer and put it into the desulfurization device for desulfurization treatment, and record the desulfurization time.

[0059] Example 3

[0060] (1) Preparation method: Red mud, polymer foam microspheres with a particle size of 35 to 50 μm, sodium silicate, fly ash, and calcium hydroxide are weighed in a mass ratio of 5:1:2:1.5:3, ball-milled for 4 h, and fully mixed. The mixed materials are extruded into strips, dried at 85° C. for 2 h, and calcined at 550° C. for 3 h to obtain a dry desulfurizer.

[0061] (2) Desulfurization: Grind the above dry desulfurizer and put it into the desulfurization device for desulfurization treatment, and record the desulfurization time.

[0062] Example 4

[0063] (1) Preparation method: Red mud, polymer foam microspheres with a particle size of 35 to 50 μm, sodium silicate, fly ash, and calcium hydroxide are weighed in a mass ratio of 9.5:2.5:4:3:6, ball-milled for 4 h, and fully mixed. The mixed materials are extruded into strips, dried at 85° C. for 2 h, and calcined at 550° C. for 3 h to obtain a dry desulfurizer.

[0064] (2) Desulfurization: Grind the above dry desulfurizer and put it into the desulfurization device for desulfurization treatment, and record the desulfurization time.

[0065] Example 5

[0066] (1) Preparation method: Red mud, polymer foam microspheres with a particle size of 35 to 50 μm, sodium silicate, fly ash, and Ca(OH)2 were weighed in a mass ratio of 5:1:2:1.5:3, ball-milled for 4 h, and fully mixed. The mixed materials were extruded into strips, dried at 85 °C for 2 h, and calcined at 650 °C for 3 h to obtain a dry desulfurizer.

[0067] (2) Desulfurization: Grind the above dry desulfurizer and put it into the desulfurization device for desulfurization treatment, and record the desulfurization time.

[0068] Example 6

[0069] (3) Preparation method: Red mud, polymer foam microspheres with a particle size of 35 to 50 μm, sodium silicate, fly ash, and calcium hydroxide are weighed in a mass ratio of 5:1:2:1.5:3, ball-milled for 4 h, and fully mixed. The mixed material is extruded into strips, dried at 85°C for 2 h, and calcined at 450°C for 3 h to obtain a dry desulfurizer.

[0070] (4) Desulfurization: Grind the above dry desulfurizer and put it into the desulfurization device for desulfurization treatment, and record the desulfurization time.

[0071] Comparative Example 1

[0072] (1) Preparation method: Red mud, activated carbon, sodium silicate, fly ash and calcium hydroxide were weighed in a mass ratio of 7:1:2.5:2:4, ball-milled for 4 h, fully mixed, and the mixed materials were extruded into strips, dried at 85 °C for 2 h, and calcined at 550 °C for 3 h to obtain a desulfurizer.

[0073] (2) Desulfurization: After grinding the desulfurizer sample, place it in the desulfurization device for desulfurization treatment, and record the desulfurization time. (The only difference from Example 2 is that the polymer foam microspheres with a particle size of 35 to 50 μm are replaced with activated carbon)

[0074] Comparative Example 2

[0075] (1) Preparation method: Red mud, activated carbon, sodium silicate, fly ash and calcium hydroxide were weighed in a mass ratio of 5:1:2:1.5:3, ball-milled for 4 h, and fully mixed. The mixed materials were extruded into strips, dried at 85 °C for 2 h, and calcined at 550 °C for 3 h to obtain a desulfurizer.

[0076] (2) Desulfurization: After grinding the desulfurizer sample, place it in the desulfurization device for desulfurization treatment, and record the desulfurization time. (The only difference from Example 3 is that the polymer foam microspheres with a particle size of 35 to 50 μm are replaced with activated carbon)

[0077] Comparative Example 3

[0078] (1) Preparation method: Red mud, activated carbon, sodium silicate, fly ash, and calcium hydroxide were weighed in a mass ratio of 5:1:2:1.5:3, ball-milled for 4 hours, and fully mixed. The mixed materials were extruded into strips, dried at 85°C for 2 hours, and calcined at 650°C for 3 hours to obtain the sample of Comparative Example 3. (The only difference from Example 5 is that the polymer foamed microspheres with a particle size of 35 to 50 μm are replaced with activated carbon)

[0079] (2) Desulfurization: The desulfurizer sample is ground and placed in a desulfurization device for desulfurization treatment, and the desulfurization time is recorded.

[0080] The performance of the desulfurizer prepared in the comparative example and the embodiment of the present invention is tested below. The desulfurizer is placed in a desulfurization test device for desulfurization treatment. The desulfurization test device mainly consists of a simulated SO2 flue gas with a concentration of 2000ppm, a reaction absorption tower and a detection device (phenolphthalein indicator). The reaction temperature is controlled at 250°C and the air velocity is 3000h -1 , measure the penetration time and penetration sulfur capacity of the desulfurizer to characterize the performance of the desulfurizer. The performance indicators of flue gas desulfurizer: penetration time, penetration sulfur capacity, specific surface area. The specific detection methods of each indicator are as follows:

[0081] Penetration time detection method: penetration time = T1-T0

[0082] T0: starting time of desulfurization experiment;

[0083] T1: fading time of phenolphthalein indicator;

[0084] Penetration sulfur capacity detection method: penetration sulfur capacity = C1-C0;

[0085] C1: The sulfur content adsorbed when the desulfurized sample is completely penetrated by SO2;

[0086] C0: initial sulfur content of the desulfurized sample when no SO2 is adsorbed;

[0087] The test results are shown in Table 1-2.

[0088] Table 1 shows the performance test data of the desulfurizers prepared in the examples and comparative examples.

[0089] Table 1

[0090] Group Breakthrough time / min Breakthrough sulfur capacity / % <![CDATA[Strength / N·cm -1 > Desulfurizer sample number Comparative Example 1 102 8.982 89 D1 Comparative Example 2 162 11.351 97 D2 Comparative Example 3 115 9.031 106 D3 Example 1 264 14.925 132 S1 Example 2 407 18.14 137 S2 Example 3 498 20.274 142 S3 Example 4 326 16.848 133 S4 Example 5 442 18.816 144 T1 Example 6 464 19.433 129 T2

[0091] Table 2 shows the specific measurement results of the pore structure and specific surface area of ​​the desulfurizer prepared in Example 3 and Example 4.

[0092] Table 2

[0093] sample <![CDATA[BET specific surface area / m 2 ·g -1 > <![CDATA[Pore volume / cm·g -1 > Average pore size / nm Example 3 25.6481 0.044833 20.3022 Example 4 19.0365 0.034136 20.0693

[0094] As shown in Table 2, the specific surface area, pore volume and average pore diameter of Example 3 are higher than those of Example 4, and the adsorption capacity is better.

[0095] Figure 2XRD pattern comparison diagram of the desulfurizer prepared in Example 3 before and after desulfurization. As can be seen from the figure, the main minerals contained in the prepared desulfurizer before and after desulfurization are hematite (Fe2O3), calcite (CaCO3), quartz (SiO2), and mullite (3Al2O3·2SiO2). The diffraction peaks of hematite hardly change before and after desulfurization, and the main phase of the desulfurizer composition remains Fe2O3. However, the diffraction peak intensities of hematite and calcite become weaker after desulfurization, indicating that Fe2O3 and CaCO3 are the effective desulfurization components in the desulfurizer and react with SO2 in the flue gas. After desulfurization, the diffraction peak of anhydrite appears, further indicating that the desulfurizer reacts with SO2 to form CaSO4. No characteristic peaks of other products are observed in the XRD pattern, probably because the content of other products is relatively low and cannot be detected by XRD.

[0096] Figure 3 In (a) and (b) are SEM photos of the desulfurizer prepared in Example 3 before and after desulfurization respectively. As can be seen from the figure, before desulfurization, the desulfurizer is formed by agglomeration of irregularly shaped and sized particles, and there are a large number of pores on the surface, which is beneficial for transporting SO2 and providing a reaction surface, creating conditions for adsorption and chemical reactions. After desulfurization, the microstructure of the desulfurizer changes significantly. During the desulfurization process, the solid-phase substances in the desulfurizer participate in the reaction, are continuously consumed, and decomposed into many small particles, and the microstructure becomes loose.

[0097] Figure 4 In (a) and (b) are the adsorption-desorption isotherms and pore size distribution diagrams of nitrogen for the desulfurizers prepared in Example 3 and Example 4 respectively. According to the IUPAC classification method, both isotherms belong to type II isotherms. When the relative pressure P / P0 < 0.05, there is a strong interaction between the desulfurizer surface and SO2, and monolayer adsorption occurs. When P / P0 is in the range of 0.05 - 0.7, with the increase of the relative pressure, multi-molecular layer adsorption begins. When 0.7 < P / P0 < 1, the adsorption amount increases rapidly, capillary condensation occurs and an H3-type hysteresis loop is generated. The generation of the hysteresis loop indicates that the pore structure of the desulfurizer is irregular. It can also be seen from the pore size distribution diagram that the two desulfurizers are mainly composed of micropores and mesopores. This porous structure is beneficial for the adsorption and transmission of gas molecules and can provide an abundant reaction surface and store products.

[0098] Figure 5 Desulfurization performance diagram of the desulfurizers prepared in the examples and comparative examples. As Figure 5 can be seen from a in the figure, under the same conditions, the desulfurizer prepared using polymer foamed microspheres as the pore-forming agent has a better desulfurization effect and a greater improvement in desulfurization efficiency. The S3 desulfurizer shows the best desulfurization performance.

[0099] It can be seen from the above embodiments and comparative examples that the dry desulfurizer provided by the present invention has a simple preparation process, high desulfurization efficiency, can realize solid waste utilization and treat waste with waste, and can be used for factory flue gas desulfurization.

[0100] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A dry desulfurization agent, characterized in that: Calculated by weight, the raw materials include 30-60 parts of red mud, 5-10 parts of pore-forming agent, 10-20 parts of binder and 20-40 parts of additives.

2. The dry desulfurization agent according to claim 1, characterized in that: The pore-forming agent is a polymer foamed microsphere with a particle size of 10 to 50 μm.

3. The dry desulfurization agent according to claim 1, characterized in that: The binder is at least one of cellulose, sodium silicate and kaolin.

4. The dry desulfurization agent according to claim 1, characterized in that: The additive is at least one of fly ash, iron powder and calcium hydroxide.

5. A method for preparing a dry desulfurization agent according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing and ball-milling the raw materials according to their weight fractions to obtain a mixed material; The mixed material is extruded and calcined to obtain the dry desulfurization agent.

6. The method for preparing a dry desulfurization agent according to claim 5, characterized in that: The calcination temperature is 400-700° C. and the calcination time is 3 hours.

7. Use of the dry desulfurization agent according to any one of claims 1 to 4 in treating sulfur-containing waste gas.

Citation Information

Cited By

  • Method for preparing flue gas desulfurizer from phosphate tailings and multiple solid wastes and application of flue gas desulfurizer

    CN121156013A